Meningkatkan Literasi Kesehatan Melalui Pojok Literasi Inklusif: Upaya Pencegahan Stunting Berbasis Teknologi di Pedesaan Kalimantan Selatan: Enhancing Health Literacy Through an Inclusive Literacy Corner: A Technology-Based Approach to Stunting Prevention in Rural South Kalimantan - Hendera, Hendera; Yunus, Muhammad; Fitriah, Aziza; Nadilla, Dhea; Dewi, Alya Puspita; Hidayah, Alfina; Rijal, Muhammad; Anggraini, Pitria; Hidayatullah, Rahmat; Susanti, Marisa; Putri, Annisa (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
The community service program